Getting to innovation : how asking the right questions generates the great ideas your company needs - VanGundy, Arthur B. (AMACOM, 2007)
Getting to Innovation How to write positioning and rationale statements for each challenge How to link together multiple objectives in priority frameworks The top 10 techniques for generating creative ideas Tips for designing and running brainstorming retreats Advice on how to select the best ideas from the many that have been generated When it comes to true innovation, it's not formulating the great ideas, but asking the right questions that will ultimately lead to results. Getting to Innovation offers the tools to help every company tap into its most inspired thinking.